Piercing the corporate veil: development of the approach - Grinšpane, Alina (Riga Graduate School of Law, 2020)
For the purpose of developing the economic growth within the market, the corporate structure has always been of great advantage. It was first understood how much of essence it is back in the 17th century when the first big companies were established. With time, limited liability of the investors was introduced, which became one of the main elements of the corporate structure together with separate legal personality. The thesis focuses on the concept of limited liability and separate legal personality of the corporate entities and how they can be challenged in the light of the fact that these core principles have always been highly protected by the legislators and the courts. One of the theories for ignoring these principles and the corporate veil, that protects the shareholders and separates them from the rights and liabilities of the entity is piercing the corporate veil. Within this Thesis, the author will provide the concept and main challenges, by discussing its application in the relevant court decisions of two jurisdictions – Latvia and England and Wales.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Liability